Pengaruh Aksesibilitas, Konektivitas, Kualitas Pelayanan, dan Kepuasan Penumpang terhadap Loyalitas Penumpang Mass Rapid Transit (MRT) Jakarta: The Influence of Accessibility, Connectivity, Service Quality, and Customer Satisfaction Towards Passenger Loyalty on Jakarta Mass Rapid Transit (MRT) - Christiani, Agustina; Kayrra, Aqila (Universitas Katolik Parahyangan, 2024)
Traffic congestion is one of the main problems faced by people in Jakarta. In fact, the government has already provided various public transportation services to overcome the traffic congestion. However, it seems that people, especially in Jakarta, prefer to travel using their private vehicles. The accumulation of private vehicles is one factor contributing to the traffic congestion in Jakarta, which is difficult to overcome. Therefore, it is necessary to examine what factors can influence passenger’s loyalty to using public transportation, in this case, the MRT Jakarta. In this research, the direct and indirect effects of accessibility, connectivity, and service quality factors will be tested on passenger loyalty through the passenger satisfaction factors. The sampling method used in this research is purposive sampling with the inverse square root method to determine the minimum sample. The data will be processed by using Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. As a result, it was found that the factors that directly influence passenger satisfaction are accessibility, connectivity, and quality of service. The factors that directly affect passenger loyalty are connectivity and passenger satisfaction. Lastly, the two factors that indirectly affect passenger loyalty through satisfaction are accessibility and service quality. From the results of this study, it is suggested that the MRT Jakarta management can improve MRT connectivity by shortening the waiting time between station stops, providing clarity regarding information for the next stop, clarity of information for passengers to make transfers with other modes of transportation, and convenience in transferring using other modes of transportation. With improved connectivity, accessibility, and quality of MRT services, passenger loyalty is hoped to increase.